2020
DOI: 10.1063/5.0020549
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of extraordinary acoustic transmission using cascaded both-sides-open disk resonator array

Abstract: Extraordinary acoustic transmission (EAT) through cascaded both-sides-open disk resonators (BSODRs) in a square lattice array (SLA) is investigated. A single BSODR consists of one disk cavity that is sandwiched by two tubes. These structures are realized by stacking perforated steel plates and immersing them in water. EAT is studied through single-layer, two-layer, three-layer, and four-layer BSODRs in SLAs. The EAT orders increase with increasing numbers of cascading layers. The quality factors of the highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…(1,2) The special sound wave modulation ability enables good design of phononic crystals for sensing. (3,4) Before using the phononic resonator to design specific sensors, the fundamental characteristics of the phononic crystals should first be investigated. The elastic moduli include mass density and elastic coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…(1,2) The special sound wave modulation ability enables good design of phononic crystals for sensing. (3,4) Before using the phononic resonator to design specific sensors, the fundamental characteristics of the phononic crystals should first be investigated. The elastic moduli include mass density and elastic coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…Based on proximity effects, Tao et al 13) designed an acoustic heterojunction to obtain a high transmission efficiency. Lee et al 14) constructed an array of both sides-open disk resonators and achieved a low-frequency extraordinary transmission in water. Devaux et al 15) proposed a resonant meta-atom and demonstrated that sound waves can be squeezed through a nanoscale channel, which showed extraordinary transmission.…”
mentioning
confidence: 99%